Proses Pengolahan Terasi Udang Sabu (Baring) dan Pemasaran Produk Secara Online di Gampong Gosong Telaga Selatan, Aceh Singkil - Saputra, Indraman; Baitia, Raji; Berutu, Yeni Marsalina Br; Syahruna, Diki; Aulia, Mizan; Nurjannah, Siti; Julita, Risma Ratna Sari; Nasution, Aswin; Aminah, Siti; Sufriadi, Sufriadi (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity was carried out in Gampong Gosong Telaga Selatan, Aceh Singkil District. The target partners were a group of fishermen who made shrimp paste and women who processed shrimp paste (baring). Based on the preliminary survey, the fishermen group faced two main problems, namely production and marketing aspects. In the production aspect, there is no standardization in the processing of shrimp paste. While in the marketing aspect, the community still uses conventional methods and has not utilized the digital platform. This research aims to analyze the processing process of sabu shrimp paste and implement an online product marketing strategy. The method used is descriptive research with a qualitative approach through interviews and observations. The results showed that with the standardization of the processing process and the use of the marketplace, there was an increase in product quality and expansion of marketing reach. Online marketing facilitates the management of orders and payments, and increases product exposure to a wider market share. This activity is expected to increase product selling value and economic welfare of the fishing community in Gampong Gosong Telaga Selatan.